2007
DOI: 10.1007/s11064-006-9235-3
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Linkage and Association Across the Dihydrolipoyl Dehydrogenase Gene Region with Alzheimer’s Disease in Three Sample Populations

Abstract: Prior case-control studies from our laboratory of a population enriched with individuals of Ashkenazi Jewish descent suggested that association exists between Alzheimer's disease (AD) and the chromosomal region near the DLD gene, which encodes the mitochondrial dihydrolipoamide dehydrogenase enzyme. In support of this finding, we found that linkage analysis restricted to autopsy-proven patients in the National Institute of Mental Health-National Cell Repository for Alzheimer's Disease (NIMH-NCRAD) Genetics Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…Studies of adult DLDHdeficient mice have suggested that a partial decrease of DLDH, which is sufficient to diminish activity of its associated enzyme complexes (Johnson, et al, 1997), results in an elevated level of susceptibility to chemical neurotoxicity (Klivenyi, et al, 2004). Moreover, variations in the DLD gene have been linked to Alzheimer's disease (Brown, et al, 2004, Brown, et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of adult DLDHdeficient mice have suggested that a partial decrease of DLDH, which is sufficient to diminish activity of its associated enzyme complexes (Johnson, et al, 1997), results in an elevated level of susceptibility to chemical neurotoxicity (Klivenyi, et al, 2004). Moreover, variations in the DLD gene have been linked to Alzheimer's disease (Brown, et al, 2004, Brown, et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, an analysis regarding the subhaplogroups of MtDNA showed that within the H haplogroup the H5 subtype showed the highest and most significant difference between AD patients and controls [49]. Other studies also reported differences in mitochondrial haplogroups in AD and many other studies are in progress on DNA and cells from different groups [50].…”
mentioning
confidence: 94%
“…Genetic association of the core metabolic enzyme DLD with late-onset AD [34]; and reduced activity of DLD-containing enzymes suggests glucose hypometabolism as a key factor in AD [36,38,444]. To determine how reduced glucose metabolism affects Aβ or tau toxicity in C.…”
Section: Chapter # Viii: General Discussionmentioning
confidence: 99%
“…Increased risk of late-onset Alzheimer's disease is genetically associated with four single nucleotide variants of dld, though how each variant specifically affects DLD enzyme activity is still unknown [34]. The dld gene encodes a core enzyme of energy metabolism in TCA cycle.…”
Section: Chapter # I: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation